2018
DOI: 10.5455/medarh.2018.72.116-119
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammatory Response Syndrome in Surgical Patients

Abstract: Objective:To determine the incidence of systemic inflammatory response of the organism in surgical patients and its impact on the outcome of treatment.Methods:A prospective study was conducted on 60 patients undergoing abdominal surgical procedures, between January 2014 and December 2015 in the Surgery Clinic at the University Clinical Center Tuzla. Two groups of thirty were formed by the method of consecutive sampling. The first group consisted of subjects who were prepared for elective abdominal surgery (lap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
1
8
0
11
Order By: Relevance
“…To date, no study of tramadol metabolism has been conducted in surgical patients with signs of acute systemic inflammation, and this is the first study to include both elective and emergency patients with inflammatory conditions. Like previous studies, this one confirmed that urgent surgical patients with clinical signs of systemic inflammation were more likely to have low ChE activity (Becher et al, 2012;Smajic et al, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…To date, no study of tramadol metabolism has been conducted in surgical patients with signs of acute systemic inflammation, and this is the first study to include both elective and emergency patients with inflammatory conditions. Like previous studies, this one confirmed that urgent surgical patients with clinical signs of systemic inflammation were more likely to have low ChE activity (Becher et al, 2012;Smajic et al, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…В основі патогенезу хірургічної травми, на думку дослідників, знаходиться системна запальна відповідь (СЗВ), яка у тяжких випадках призводить до розвитку синдрому, відомому як SIRS (від англ. Systemic inflammatory response syndrome) [3]. У деяких сприй нятливих осіб це може викликати розвиток синдрому поліорганної недостатності та смерть.…”
Section: вступunclassified
“…Навіть одинична лапаротомія здатна забезпечувати виникнення прозапального фенотипу, що включає нейроендокринний стрес, кіркову збудливість, імунну активацію, метаболічні зміни та коагулопатію [4]. Примітно, що такі складові патогенезу хірургічної травми, як психоемоційний стрес, ноцицептивні механізми, побічна дія анестетиків, крововтрата, разом з рановим процесом сприяють розвитку СЗВ [3]. Остання також є загальною реакцією організму при хронічному дифузному запаленні слабкої інтенсивності та може виявлятися за відсутності інших клінічних ознак [5].…”
Section: вступunclassified
“…This response is due to a cascade of neuroendocrine, metabolic and immunological factors. In the systemic acute inflammatory reaction, a release of pro-inflammatory cytokines (IL-1β, IL-6 and TNF) occurs as part of wound healing by producing acute phase reactants (C-reactive protein (CRP), fibrinogen and complement C3) as a reaction to the initial surgical trauma [ 11 , 12 ]. High concentrations of pro-inflammatory cytokines (predominantly IL-6) and lack of compensatory expression of anti-inflammatory cytokines may cause systemic inflammatory response syndrome (SIRS).…”
Section: Introductionmentioning
confidence: 99%